(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Il diritto di libertà religiosa tra rendicontazione sui diritti umani e Responsabilità Sociale d’Impresa - 2. Libertà religiosa, Guiding Principles on Business and Human Rights e RSI - 3. Libertà religiosa e standard nazionali: brevi osservazioni sul Piano d’Azione Nazionale (PAN) 2014-2016 sulla Responsabilità Sociale d’Impresa e 2016-2021 su Impresa e Diritti Umani - 4. Valori religiosi e valori laici nella Responsabilità Sociale d’Impresa - 5. Dall’RSI all’accountability: la rendicontazione sui diritti umani negli enti religiosi ETS e nell’Impresa sociale. Religious freedom and Corporate Social Responsibility ABSTRACT: International standards on Business and Human Rights and on Corporate Social Responsibility (CSR) define a system of rules currently in use to combat human rights violations in contemporary industrial societies. On the basis of these rules, governments adopt the so-called National Action Plans (NAPs), which also Italy has recently adopted. In this context, the protection of religious freedom plays a fundamental role as part of the range of needs of modern intercultural societies. This paper in this respect is divided into two parts. The first part investigates the role of religious freedom in international standards on Business and human rights and in the NAPs, paid attention to the Italian National Action Plans. The second part on the other hand, deals with the theme of accountability on human rights in the Italian non-profit area. In this context, the processes of accountability also involve entities who operate by expressing a certain tendency or religious aims. These entities can have a specific interest in the accountability on human rights because through the adherence to the so-called systems of Non-Financial Reporting (NFR) clearly reaffirm the values of the religious cultures of which they are the direct expression.